2012
DOI: 10.1126/scitranslmed.3004306
|View full text |Cite
|
Sign up to set email alerts
|

The Stoichiometric Production of IL-2 and IFN-γ mRNA Defines Memory T Cells That Can Self-Renew After Adoptive Transfer in Humans

Abstract: Adoptive immunotherapy using ex vivo-expanded tumor-reactive lymphocytes can mediate durable cancer regression in selected melanoma patients. Analyses of these trials have associated the in vivo engraftment ability of the transferred cells with their antitumor efficacy. Thus, there is intensive clinical interest in the prospective isolation of tumor-specific T cells that can reliably persist after transfer. Animal studies have suggested that central memory CD8(+) T cells (T(CM)) have divergent capabilities inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…Autocrine IL-2 production is part of the polyfunctional central-memory T cell profile, and our study now provides direct evidence that autocrine IL-2 production contributes to a greater expansion capacity of CD8 + T cells. Also in case of antitumor immunity, it has been suggested that IL-2 production of tumor-infiltrating CD8 + lymphocytes could be considered as a pharmacodynamic biomarker for clinical responses (32,33). However, IL-2-independent processes are likely important as well and may also be implicated in the self-renewal of central-memory CD8 + T cells (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Autocrine IL-2 production is part of the polyfunctional central-memory T cell profile, and our study now provides direct evidence that autocrine IL-2 production contributes to a greater expansion capacity of CD8 + T cells. Also in case of antitumor immunity, it has been suggested that IL-2 production of tumor-infiltrating CD8 + lymphocytes could be considered as a pharmacodynamic biomarker for clinical responses (32,33). However, IL-2-independent processes are likely important as well and may also be implicated in the self-renewal of central-memory CD8 + T cells (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53] However, there remain controversies in defining the immune response of the specific memory T subsets within antigen-specific CTL against tumor cells. 54,55 In these studies, we characterized the antitumor activities of the two different memory cell subsets, CM and EM, from XBP1 antigen-specific CTL against a variety of solid tumor cells. We chose to evaluate the XBP1-CTL after the fourth round of peptide stimulation, due to high levels of antigen-specific cells within both memory cell subsets of the CD3 C CD8 C T cells population.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, these intrinsic attributes of the CTLs derived from T CM was not compromised by the acquisition of effector cell transcriptional program such as higher IFNg and Eomes. 35 These results led to the postulation that T CM derived CTLs would perform better in both persistence and function upon adoptive transfer compared to T N/SCM derived CTLs.…”
Section: Cd62lmentioning
confidence: 99%